Improving butylhydroxytoluene activity with alternative secondary antioxidants: High synergistic effect in stabilizing biodiesel/diesel fuel blends in the presence of pro-oxidative metal - Roveda, Ana Carolina; de Oliveira, Ivan Pires; Caires, Anderson Rodrigues Lima; Rinaldo, Daniel [UNESP]; Ferreira, Valdir Souza; Trindade, Magno Aparecido Gonçalves (Elsevier, 2022)
We used butylhydroxytoluene (BHT) combined with citric acid (CA), ascorbic acid (AA), and alizarin (ALZ) to form multifunctional additives, which improves BHT activity and even lowers its concentration by half. As a result, high synergistic effect was observed against the accelerated oxidation process of all blends (biodiesel/diesel) with high content of biodiesel when submitted to thermal degradation as well as the presence/absence of pro-oxidative metals. We provide a mechanism in which ALZ is responsible for BHT regeneration because ALZ is able to donate two hydrogens from its hydroxyl groups to obtain a diketone that can subsequently be complexed with metal ions. This finding is highlighted by the ability of the multifunctional additives—when comparing with the addition of only BHT in concentration enough to achieve the same stabilizing effect—to preserve biodiesel quality during long-term storage even in the presence of pro-oxidative metal. Finally, our study demonstrates that the final cost of biodiesel could be lowered in a scalable production due to the low concentration of additives required to maintain its quality as per specifications.
Keywords: Biofuel additive; Multifunctional additives; Stabilization; Synergism; Thermodegradation